Writing killer copy for "boring" industries : learn how to personalize your voice and interact with customers - Busche, Laura (O'Reilly, 2016)
"It's pretty easy to write compelling stories about a headline making company. But what if your company isn't figuring out how to shoot humans from one city to the next in a giant vacuum tube or curing cancer or cracking encryption codes? What if your company is, well, kind of boring? How do you produce exciting and engaging stories about the nap-inducing enterprise? Content marketing ace Laura Busche tells how in this video filled with tact, grace, humor, and plenty of pithy examples. Discover four simple questions that reveal the un-boring topics hidden inside your brand. Explore the best techniques for identifying the right voice and tone to use in your copy. Understand the basics of brand personality and the importance of human speak, not robot speak. Learn to spice your content by borrowing topics from fun industries like fashion and entertainment. See how other not-so-exciting companies tell their escape-from-snoresville stories."--Resource description page.